Comparing the European and the Southeast Asian Response to Global Terrorism - Desker, Barry; Pavlova, Elena (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2005)
ABSTRACT This article examines the mechanisms for combating global terrorism which emerged in Europe and Southeast Asia in the aftermath of 11 September, the Bali bombing, the two Jakarta bombings, and the Madrid train bombings. The article argues that, despite various attempts at crafting a common security framework in each region, the most successful examples of counter-terrorism and anti-terrorism cooperation thus far have been at the bilateral and trilateral levels. In balancing between national security priorities and multilateral cooperative arrangements, the main difference between the European and Southeast Asian approach comes from the different ways in which the terrorist threat is perceived. While the European reaction is determined by the acknowledgement of a "common external threat," the Southeast Asian response is based on the recognition of a "common internal threat." Such divergence of perspectives invariably nuances the scope of national and regional initiatives in each case scenario. These are further reinforced by the ideational and operational modalities of each regional community (EU and ASEAN).